1997
DOI: 10.1148/radiographics.17.1.9017797
|View full text |Cite
|
Sign up to set email alerts
|

Overview of traumatic injury of the thoracic aorta.

Abstract: #{149} Be able to work up a trauma patient to exclude or detect thoracic aortic injury. #{149} Be familiar with general and specific radiographic signs of mediastinal hematoma and several pitfalls in evaluating trauma chest radiogr-aphs. #{149} Understand the difference between direct and indirect CT signs of aortic injury. #{149} Be able to identify vat-i-OtiS angiographic findings in aortic injury and distinguish between traumatic pseudoaneurysm and duetus diverticulum. #{149} Realize the significance of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(57 citation statements)
references
References 0 publications
0
52
0
5
Order By: Relevance
“…On the other hand, 70 % of the patients with blunt aortic lesion who reach the hospital alive will survive, if given appropriate treatment. Development of coordinated emergency medical services using ground and air support, setting of dedicated trauma centers and recent advances in diagnostic modalities may allow for a prompt and accurate diagnosis and thus improve blunt trauma patients' outcome [1,13].…”
Section: Clinical Presentation and Prognosismentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, 70 % of the patients with blunt aortic lesion who reach the hospital alive will survive, if given appropriate treatment. Development of coordinated emergency medical services using ground and air support, setting of dedicated trauma centers and recent advances in diagnostic modalities may allow for a prompt and accurate diagnosis and thus improve blunt trauma patients' outcome [1,13].…”
Section: Clinical Presentation and Prognosismentioning
confidence: 99%
“…Acute coarctation syndrome, relating to upper limb hypertension and lower limb decreased pulses and hypotension, as well as a precordial or interscapular systolic ejection murmur, is occasionally present. These symptoms and signs are neither sensitive nor specific [13,14]. In young patients with elastic chest walls involved in deceleration accidents, kinetic energy is absorbed by the intrathoracic viscera rather than by the thoracic cage itself.…”
Section: Clinical Presentation and Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…Mosquera et al [7] reported that significant aortic regurgitation (AR) developed in 12% of patients with injuries at the ascending aorta as a consequence of the thoracic trauma. Proposed mechanisms that contribute to BAI include shearing forces, rapid deceleration, hydrostatic forces, and osseous pinch [8]. Rapid deceleration in the anteroposterior and lateral directions has been shown to be sufficient to result in cardiac displacement, producing torsion and shearing forces against the aorta at levels of relative immobility, mainly the ligamentum arteriosum, aortic root, and diaphragm [9].…”
mentioning
confidence: 99%